Characterizations of PMCA2-interacting complex and its role as a calcium oxalate crystal-binding protein - Arada Vinaiphat (2019)
© 2017, Springer International Publishing AG, part of Springer Nature. Three isoforms of plasma membrane Ca 2+ -ATPase (PMCA) are expressed in the kidney. While PMCA1 and PMCA4 play major role in regulating Ca 2+ reabsorption, the role for PMCA2 remains vaguely defined. To define PMCA2 function, PMCA2-interacting complex was characterized by immunoprecipitation followed by nanoLC-ESI-Qq-TripleTOF MS/MS (IP-MS). After subtracting non-specific binders using isotype-controlled IP-MS, 474 proteins were identified as PMCA2-interacting partners. Among these, eight were known and 20 were potential PMCA2-interacting partners based on bioinformatic prediction, whereas other 446 were novel and had not been previously reported/predicted. Quantitative immuno-co-localization assay confirmed the association of PMCA2 with these partners. Gene ontology analysis revealed binding activity as the major molecular function of PMCA2-interacting complex. Functional validation using calcium oxalate monohydrate (COM) crystal-protein binding, crystal-cell adhesion, and crystal internalization assays together with neutralization by anti-PMCA2 antibody compared to isotype-controlled IgG and blank control, revealed a novel role of PMCA2 as a COM crystal-binding protein that was crucial for crystal retention and uptake. In summary, a large number of novel PMCA2-interacting proteins have been defined and a novel function of PMCA2 as a COM crystal-binding protein sheds light onto its involvement, at least in part, in kidney stone pathogenesis.